Phenolics profile, anti-nephrolithiasis, and antioxidant activities of Monodora myristica seed: impact of endogenous proteins and lipids - Emmanuel Anyachukwu Irondi; Tolulope Muktar Aroyehun; Arinze Favour Anyiam; Milan Kumar Lal (Food Production, Processing and Nutrition, 2023)
Abstract The bioactive compounds in a food matrix can exist either in their free form or bound to other endogenous compounds, which may affect their bioactivities. This study investigated the impact of endogenous proteins and lipids on the phenolics profile, anti-nephrolithiasis, and antioxidant activities of Monodora myristica (African nutmeg) seed. Endogenous proteins and lipids in M. myristica seed flour were removed by deproteinization and defatting, to obtain the deproteinized, defatted, and deproteinized-defatted flours. The native flour served as a control. Phenolics compounds in the flours were quantified using HPLC-DAD, while nephrolithiasis-associated enzymes (xanthine oxidase and urease) inhibitory and antioxidant activities were determined using a spectrophotometer. Nine phenolic compounds (gallic, chlorogenic, caffeic, p-coumaric, ellagic acids, catechin, rutin, quercetin and luteolin) were detected in the native flour, with quercetin as the most abundant. The concentrations of the phenolic compounds, nephrolithiasis-associated enzymes inhibitory, and antioxidant activities of the flour decreased significantly due to deproteinization and defatting. Overall, the native flour had the highest concentrations of phenolics and the most potent enzymes inhibitory and antioxidant activities, followed by the defatted, deproteinized, and deproteinized-defatted flours. Hence, endogenous proteins and lipids may enhance the phenolics profile, anti-nephrolithiasis and antioxidant activities of M. myristica seed. This could have application in the development of functional food products and nutraceuticals targeting nephrolithiasis. Graphical Abstract